Factors associated with the probability of common mental disorders in pregnant women: a cross-sectional study - Roselma Lucchese; Naiane Dias Simões; Luiz Henrique Batista Monteiro; Ivânia Vera; Inaina Lara Fernandes; Paulo Alexandre de Castro; Graciele Cristina Silva; Renata Alessandra Evangelista; Alexandre de Assis Bueno; Moisés Fernandes Lemos (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To estimate the prevalence of probability of common mental disorders in pregnant women and associated factors. Methods: A cross-sectional study with a quantitative and descriptive approach was performed with 330 pregnant women enrolled in a Women's Health Service located in Mid-West Brazil. Data were obtained through a questionnaire about socio-demographic characteristics and family or personal history. The Self-Reporting Questionnaire and Poisson regression were applied to screen for common mental disorders, aiming to identify factors associated with it. Results: The prevalence of probability of common mental disorders among pregnant women was 57.1% and it was associated with marital status, gestational age, unplanned pregnancy and bleeding. Conclusion: The prevalence of pregnant women likely to have common mental disorders and the average Self-Reporting Questionnaire score estimated in this study were higher than those found in other studies with samples from the general population.